Implementation of the didactic strategy of critical-reflexive thinking in the literary analysis of Shakespeare’s Hamlet - Marín-Calderón, Norman (2014)
This essay concentrates on the process of teaching execution in the critical-reflexive thinking development as a college didactic strategy when teaching literature, more specifically William Shakespeare’s Hamlet (1603). Such a strategy is based on a series of communicative activities which analyze the development of students’ cognitive abilities, their process of criticism and analysis, their personal reflection through experiential moments as well as the development of techniques on argumentation and critical thinking. The purpose of this strategic implementation was to improve students’ academic quality in their critical and argumentative productions when analyzing Hamlet as a literary text.